2021
DOI: 10.1371/journal.pone.0254060
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and coincidence of pollution, climate impacts, and health risk in the Anthropocene

Abstract: Previous research demonstrates that low-income countries face higher risks than high-income countries from toxic pollution and climate change. However, the relationship between these two risks is little explored or tested, and efforts to address the risks are often independent and uncoordinated. We argue that the global risks from toxic pollution and climate change are highly correlated and should be jointly analyzed in order to inform and better target efforts to reduce or mitigate both risks. We provide such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…The stride to achieve industrialization and urbanization has introduced various environmental challenges [1,2]. Firstly, it has led to the destruction of landscape, ecosystems and exacerbated the climate change crisis [3,4]. Secondly, it has accelerated the introduction and transport of legacy contaminants, threatening the existence of humans, the environment and other organisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…The stride to achieve industrialization and urbanization has introduced various environmental challenges [1,2]. Firstly, it has led to the destruction of landscape, ecosystems and exacerbated the climate change crisis [3,4]. Secondly, it has accelerated the introduction and transport of legacy contaminants, threatening the existence of humans, the environment and other organisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental issues are crucial because they involve the interests of human rights [4]. Various environmental problems include pollution, climate change, depletion of natural resources, waste disposal, loss of biodiversity, deforestation, and depletion of the ozone layer [5]. In general, pollution is the first environmental issue.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, although Africa contributes only an estimated 2%–3% of global greenhouse gas emissions, a recent report from the World Meteorological Organization (WMO) indicated that the continent suffers a disproportionate environmental impact, including rising temperatures, drought and water stress due to flooding and rising seas [ 1 ]. Research from 2022 analysing combined data from the Notre Dame–Global Adaptation Index (ND-GAIN), environmental performance index, and the Global Alliance on Health and Pollution demonstrated that ‘the highest climate and toxic pollution risks appear to coincide in the same countries’ which are ‘geographically concentrated across the African continent’ [ 2 ]. These findings align with over a decade of warnings produced by earlier research, such as the African Development Bank’s 2011 report which stated, ‘as a percentage of gross domestic product (GDP), climate damages in Africa are expected to be higher than in any other region in the world, more than 10% higher than the next exposed region (India) and more than twice as high as in the US, Russia, Eurasia, and Latin America’ [ 3 ].…”
Section: Introductionmentioning
confidence: 99%